Islam Nusantara: Islam Khas dan Akomodatif terhadap Budaya Lokal - Edi Susanto; Karimullah Karimullah (Al-Ulum, 2016)
This article is mainly to analyse background of the emerging of an Islamic thought, that is, friendly Indonesian model. This study has been conducted in order to address the spread of Islamic literalist-puritans-literalist-trans-nationalist massively and fiercely against local traditions. In this study, we look at the emerging a new Indonesian model of Islam, that is, the so called â€œIslam Nusantaraâ€. The Islam Nusantara is believed basically rooted from Indonesiansâ€™ tradition and has already grown in the early age of Islam in this country which was introduced by the Walisongo (the nine priests). Hence, Islam Nusantara should not be seen in suspicious perspective since it has been basically familiar with cultures and characters of Indonesian nation, which are moderate and tolerant ones. Moreover, it figures out the role of Pesantren institutions, and organisations such as NU and Muhammadiyah with their various characteristics, strength and weakness, are the pioneer of Islam Nusantara heritage and cultures.